2007
DOI: 10.1002/asi.20642
|View full text |Cite
|
Sign up to set email alerts
|

Matrix comparison, Part 2: Measuring the resemblance between proximity measures or ordination results by use of the mantel and procrustes statistics

Abstract: The present two-part article introduces matrix comparison as a formal means for evaluation purposes in informetric studies such as cocitation analysis. In the first part, the motivation behind introducing matrix comparison to informetric studies, as well as two important issues influencing such comparisons, matrix generation, and the composition of proximity measures, are introduced and discussed. In this second part, the authors introduce and thoroughly demonstrate two related matrix comparison techniques the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 55 publications
1
49
0
1
Order By: Relevance
“…This technique computes a covariant statistic between the two matrices, and then tests it against the null hypothesis of "no association" based on a nonparametric distribution obtained from permuting rows and columns together in one matrix. Several covariant statistics have been designed for different purposes, and we chose the Spearman rank correlation, ρ M , as recommended in [17].…”
Section: Resultsmentioning
confidence: 99%
“…This technique computes a covariant statistic between the two matrices, and then tests it against the null hypothesis of "no association" based on a nonparametric distribution obtained from permuting rows and columns together in one matrix. Several covariant statistics have been designed for different purposes, and we chose the Spearman rank correlation, ρ M , as recommended in [17].…”
Section: Resultsmentioning
confidence: 99%
“…We used the standardized Mantel statistic (r M ), calculated using Eq. (2) from Schneider and Borlund (2007), to determine if there was a linear correlation between genetic and discrete trait proximity matrices. This correlation coefficient is easily interpretable and informative as a descriptive measure, because the coefficient is bounded between 21 and 11.…”
Section: Mantel Testsmentioning
confidence: 99%
“…The Procrustes analysis is an improvement of the Mantel test (Mantel, 1967), which is becoming a popular measure of the association between distance matrices. It has been found that the Procrustes analysis is more sensitive to type I error rates and to power of significance tests compared to the Mantel test (Peres-Neto & Jackson, 2001;Schneider & Borlund, 2007). There are two additional features of the Procrustes analysis that make it more appropriate for the case study considered in this paper.…”
Section: Methodsmentioning
confidence: 95%